Long non-coding RNA HOTAIR regulates myeloid differentiation through the upregulation of p21 via miR-17-5p in acute myeloid leukaemia. Issue 10 (3rd October 2021) - Hu, Linhui; Liu, Jun; Meng, Ye; Zheng, Huimin; Ding, Chen; Wang, Huiping; Charwudzi, Alice; Li, Manman; Li, Jingrong; Zhai, Zhimin; Xiong, Shudao
ABSTRACT: Long non-coding RNA HOTAIR has been reported to play a key role in regulating various biological processes in various cancers. However, the roles and mechanisms of HOTAIR in acute myeloid leukaemia (AML) are still unclear and need to be investigated. In this study, we induced differentiation of four AML cell lines by all-trans retinoic acid (ATRA) and found HOTAIR was significantly upregulated in the process. Chromatin immunoprecipitation (ChIP) assays indicated that C/EBPβ upregulated HOTAIR during ATRA induced differentiation in HL-60 cells. By gain- and loss-of-function analysis, we then observed that HOTAIR expression was positively correlated with ATRA-induced differentiation and negatively regulated G1 phase arrest in HL-60 cells. In addition, we found that HOTAIR promoted ATRA-induced differentiation via the regulation of the cell cycle regulator p21 via miR-17-5p. Moreover, we detected the expression of HOTAIR in 84 de novo AML patients, HOTAIR was found significantly downregulated in the AML patients compared to the iron deficiency anaemia (IDA) control group, negatively correlated with the platelet level in M2 patients. In all, our data suggest that HOTAIR may be subtype-specific in AML-M2 patients, also HOTAIR regulates AML differentiation by C/EBPBβ/HOTAIR/miR-17-5p/p21 pathway. The findings of the present study provide a novel insight into the mechanism of lncRNA-mediated differentiation and indicate that HOTAIR may be a promising therapeutic target for leukaemia, especially for AML with M2 type. Abbreviation: AML: acute myeloid leukaemia; APL: acute promyelocytic leukaemia; ATRA: all-trans retinoic acid; CCK8: cell Counting Kit-8; CDKs: cyclin-dependent kinases ; CeRNA: competing endogenous RNAs; ChIP: chromatin immunoprecipitation; CHX: cycloheximide; FAB: French–American–British; FCM: flow cytometry; HOTAIR: HOX transcript antisense RNA; IDA: iron-deficiency anemia; lncRNA: long non-coding RNA; 3′UTR: 3′untranslated region; MT: Mutation type; WT: Wild type; qRT-PCR: Quantitative real-time PCR